1995
DOI: 10.1159/000119185
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Drugs and Psychomotor Performance

Abstract: Nearly all antidepressants are tested psychometrically in order to detect side effects of these drugs. Based on a review of the relevant published data on critical flicker fusion frequency measurements, simple reaction time, complex reaction time, tracking, tapping, and car driving simulation measurements, the underlying principles of the different effects of these drugs in healthy volunteers are discussed. It seems that essentially the sedative properties of a compound are important rather than e.g. specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…Trazodone, by contrast, did not signiÞcantly impair performance on any of the tasks used in the present study, which is concordant with some previous studies and discordant with others (Curran et al 1988;Sakulsripong et al 1991;Amado-Boccara et al 1994;Volz and Sturm 1995). The present study found that trazodone did not impair performance on the DSST, which is generally concordant with previous studies that included this procedure (for a review see AmadoBoccara et al 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Trazodone, by contrast, did not signiÞcantly impair performance on any of the tasks used in the present study, which is concordant with some previous studies and discordant with others (Curran et al 1988;Sakulsripong et al 1991;Amado-Boccara et al 1994;Volz and Sturm 1995). The present study found that trazodone did not impair performance on the DSST, which is generally concordant with previous studies that included this procedure (for a review see AmadoBoccara et al 1994).…”
Section: Discussionsupporting
confidence: 92%
“…Like the benzodiazepines, acute administration of trazodone signiÞcantly impairs performance on several laboratory tasks (for reviews see Woods et al 1987Woods et al , 1992Amado-Boccara et al 1994;Curran et al 1988;Volz and Sturm 1995). These Þndings suggest that the behavioral pharmacological proÞle of trazodone is qualitatively similar to that of commonly prescribed benzodiazepine hypnotics.…”
Section: Introductionmentioning
confidence: 97%
“…A 0.1-unit decrease in SI represents 10% of the scale on this measure, which ranges from 0 (chance performance) to 1.0 (perfect discrimination). A 100-msec increase in RT is characteristic of deficits observed in rats in a variety of attention tasks (e.g., Pang etal, 1993;Bushnell, 1995;Ward and Brown, 1996) and represents a large and adverse change in studies of human reaction time (Volz and Sturm, 1995). Both of these effect levels were previously associated with statistically-significant decrements in signal detection during inhalation of toluene (Bushnell et al, 1994).…”
Section: O 1997 Society Of Toikoksgymentioning
confidence: 95%
“…Daten nach Antidepressivaeinnahme über mehr als 10 Tage liegen nur vereinzelt vor [30,36]. In den letzten Jahren wurden u. a. von der eigenen Arbeitsgruppe umfangreiche, aufwendige Untersuchungen an depressiven Patienten durchgeführt [10,11,25,26].Die bislang vorliegenden Ergebnisse lassen sich dahingehend zusammenfassen, dass selektive Antidepressiva wie SSRIs (Citalopram, Fluoxetin, Fluvoxamin, Paroxetin, Sertralin), Mirtazapin und Moclobemid im Gegensatz zu vielen trizyklischen Antidepressiva [25,32] zu keinen signifikanten Beeinträchtigungen kognitiver und psychomotorischer Leistungsparameter führen.…”
Section: Alkoholmissbrauch Und -Abhängigkeitunclassified